Clinical characteristics of long‐term survival with noninvasive ventilation and factors affecting the transition to invasive ventilation in amyotrophic lateral sclerosis. Issue 6 (28th August 2018) - Hirose, Takahiko; Kimura, Fumiharu; Tani, Hiroki; Ota, Shin; Tsukahara, Akihiro; Sano, Eri; Shigekiyo, Taro; Nakamura, Yoshitsugu; Kakiuchi, Kensuke; Motoki, Mikiko; Unoda, Kiichi; Ishida, Simon; et al.
ABSTRACT: Introduction : We evaluated post–noninvasive ventilation survival and factors for the transition to tracheostomy in amyotrophic lateral sclerosis (ALS). Methods : We analyzed 197 patients using a prospectively collected database with 114 patients since 2000. Results : Among 114 patients, 59 patients underwent noninvasive ventilation (NIV), which prolonged the total median survival time to 43 months compared with 32 months without treatment. The best post‐NIV survival was associated with a lack of bulbar symptoms, higher measured pulmonary function, and a slower rate of progression at diagnosis. The transition rate from NIV to tracheostomy gradually decreased over the years. Patients using NIV for more than 6 months were more likely to refuse tracheostomy and to be women. Discussion : This study confirmed a positive survival effect with NIV, which was less effective in patients with bulbar dysfunction. Additional studies are required to determine the best timing for using NIV with ALS in patients with bulbar dysfunction. Muscle Nerve 58 :770–776 2018